Evaluate Silurian Drainage Jalan Raya A. Y Patty Kecamatan Sirimau Kota Ambon - Juensi Stela Sabono; Renny James Betaubun; Edison Hukom (KOLONI, 2024)
In general, drainage is an attempt to drain excess water in a certain context of use. If there is a problem with drainage, it will cause puddles on the surface of the highway. One of the roads that experienced puddles is A.Y. Patty Sirimau District, Ambon City. The drainage channel is not able to accommodate rainwater runoff which results in an increase in water discharge resulting in puddles on the highway. Therefore, it is necessary to evaluate the drainage channel of A.Y. Patty Sirimau District, Ambon City, to determine the dimensions of the existing canal, population growth, household dirty water disposal that enters the drainage channel and runoff discharge on the highway. From the results of calculations and analysis, it is obtained that the projected population in the 10th year is 2,9 1 18 people with discharge discharge (Qab) = 0.006955 m3/sec/ha and runoff discharge on the A.Y highway. Patty Sirimau District, Ambon City is Qs = 19.87599 m3/s, Or = 0.06341 m3/s with a difference in discharge of 19.81258 m3/s. So that the capacity of the drainage channel meets and is still suitable for use.